Effects of Aronia polyphenols on the physico-chemical properties of whey, soy, and pea protein isolate dispersions - Mackenzie M. Hansen (BMC, 2021)
Abstract Bioactive compounds including polyphenols (PP) have been observed to naturally form non-covalent complexation interactions with proteins under mild pH and temperature conditions, affecting protein structures and functionality. Previously, addition of Aronia berry PP to liquid dispersions containing whey protein isolate (WPI) and sucrose was found to alter characteristics including viscosity, surface tension, and particle sizes, with changes being attributed to protein-PP interactions. In this study we aimed to investigate whether Aronia PP would interact with soy and pea protein isolates (SPI and PPI, respectively) to a similar extent as with WPI in liquid protein-sucrose-PP mixtures. We hypothesized that formulations containing PPI (comprised of larger proteins) and hydrolyzed SPI (containing more carboxyl groups) may exhibit increased viscosities and decreased aggregate sizes due to enhanced protein-PP interactions. Concentrated liquid dispersions of varied ratios of protein to sucrose contents, containing different protein isolates (WPI, SPI, and PPI), and varied Aronia PP concentrations were formulated, and physical properties were evaluated to elucidate the effects of PP addition. PP addition altered physical characteristics differently depending on the protein isolate used, with changes attributed to protein-PP interactions. SPI and PPI appeared to have higher propensities for PP interactions and exhibited more extensive shifts in physical properties than WPI formulations. These findings may be useful for practical applications such as formulating products containing fruit and proteins to obtain desirable sensory attributes. Graphical abstract